2004
DOI: 10.1007/s11661-004-0185-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on the low-cycle fatigue behavior and deformation structure of INCONEL 718 at 650 °C

Abstract: Symmetrical push-pull low-cycle fatigue (LCF) tests were performed on INCONEL 718 (IN718) containing 12, 29, 60, and 100 ppm B at 650 °C. The results showed that all the alloys experienced a relatively short period of initial cyclic hardening at low strain amplitudes, followed by a regime of saturation or slightly continuous cyclic softening. The initial cyclic hardening phase decreased with increasing strain amplitudes, and disappeared at the high strain amplitudes. A serrated flow was observed in the plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
(62 reference statements)
1
14
0
2
Order By: Relevance
“…[1,2] Alloy IN718 is one of those alloys that exhibit planar slip behavior. [3][4][5][6][7][8][9][10][11][12][13] Planarity of slip is known to be enhanced by shearable precipitates. Thus, planar slip deformation under such microstructural conditions promotes the tendency of strain localization in the initially active slip bands.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Alloy IN718 is one of those alloys that exhibit planar slip behavior. [3][4][5][6][7][8][9][10][11][12][13] Planarity of slip is known to be enhanced by shearable precipitates. Thus, planar slip deformation under such microstructural conditions promotes the tendency of strain localization in the initially active slip bands.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few studies have reported the influence of B on either the microscopic deformation mechanism or the low-cycle fatigue (LCF) properties of nickel-base superalloys. [15] It was, therefore, considered necessary to further study the effect of B on the plastic deformation mechanism, especially at room temperature (RT), at which the grain boundaries may not play a significant role in plastic deformation of IN 718 and especially during LCF, which was the primary goal of this work.…”
mentioning
confidence: 99%
“…In all the fatigue tests conducted in this study, the cycling frequency was f cycle = 2 Hz and the load ratio ( min / max in LCF and min / max in HCF) was R = 0.1. The nominal life of the fully hardened IN718 material exposed to VLCF was estimated as N VLCF = 250 cycles [15][16][17][18]. Seven specimens were low-cycle fatigued (LCF) under more typical peak strain of max = 1.2%.…”
Section: -4mentioning
confidence: 99%